(untitled) (Innovative professional education, 2025)
The work on the formation of logical memory, not mnemonic, on the formation of thinking in the process of professional training in higher education prepares the ground for the comprehensive development of a specialist in the process of self-education in professional activity. In the process of professional training, in order to master the methods and techniques of searching for and acquiring knowledge, it is necessary to ensure that students develop the following mental activity techniques: analysis, comparison, juxtaposition, classification, analogy, systematization, generalization, etc.